LOCAL POTENTIAL BASED TOURISM VILLAGE DEVELOPMENT - Purnamasari, Irma; Rahmawati, Rita; Luthfie, Muhammad; Mardiah, Mardiah; Apriliani, Afmi; Tri Ramdani, Faisal; Sastrawan, Berry; Pratami, Mirna; Salopah,; Ranbilal, Rio; Tirtayasa,; Ubaidilah, Asep (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
One of the problems around the forest is the very high dependence of the community on the forest. Forests are a source of life for the people, but on the one hand, forests must also be preserved. For this reason, it is necessary to look for new livelihoods, which still utilize forests but do not damage their sustainability. The choice is environmental tourism services. Against this background, this community service activity aims to increase the community's knowledge and skills regarding governance and tourism development. The method used in this service is by means of observation or surveys, counselling, training, mentoring, and product manufacturing skills. The results of the activity show an increase in knowledge and skills as measured by the pretest and post-test instruments. The community response to this activity was very positive. The community has new knowledge about how to take advantage of the local potential to become village tourism objects.